Pengembangan Bahan Ajar Berbasis Bahan Cerita Aku Bisa Mengasihi Orang Lain (Yohanes 12:34-35) Dalam Pembelajaran Pendidikan Agama Kristen Dan Budi Pekerti Kelas III SD Di Kecamatan Sipoholon Kabupaten Tapanuli Utara - Anita Manullang (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The aim of this research is to develop a product in the form of story-based teaching materials for the subjects of Christian Religious Education and Character Education for class III elementary school and to determine the suitability of the teaching materials developed. The method used is research and development (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The data obtained was analyzed descriptively qualitatively and descriptively quantitatively. Based on the results of research at the analysis stage, the overall average result of the 11 PAK teachers' answers was 3.60, which stated that the score was in the "Very High" category, meaning that the PAK class III elementary school teachers strongly agreed with using story-based teaching materials as learning material in Aku. Can Love Others. At the design stage, the product is designed including designing story-based teaching materials, determining the materials and reviewing subjects according to the curriculum. The development stage contains activities to design and assess the product. The suitability of teaching materials based on story material from the research results is "Very Good" used for learning for third grade elementary school students with the results of assessing the suitability of the material with an indicator of 88%, the suitability of the material with the learning objectives is 92%, the message/message is conveyed well and does not deviate from the theme 96%, suitability of story content with the theme of story-based teaching materials 92%, and material packaging in story-based teaching materials applied in daily life 84% showing the criteria "Very Good". Then in the implementation stage, teacher response assessment data shows that story-based teaching materials have met the criteria well as Christian Religious Education learning materials for third grade elementary school students with a score percentage of 72% in the "Good" category. The evaluation of student learning outcomes according to the RPP which was carried out showed that the effectiveness of story-based teaching materials had met the requirements, namely that out of 25 students at SD Negeri 173140 Pagar Batu, it was known that 88% of students obtained learning outcomes > 75, namely 22 students had met the minimum completeness criteria (KKM) score. , b) spiritual evaluation is known to have achieved 81.6% and is in the Good category, c) social evaluation achieved 81.4% and is in the Good category. The evaluation stage is carried out by improving the product using criticism and suggestions from validators and educators who have assessed the material story material-based teaching to provide feedback on the development of subsequent story material-based teaching materials.